Rancang Bangun Kontrol Kecepatan Cairan Infus Berbasis Arduino Uno - Sandi Youda; Juli Sardi (Dinasti Research, 2022)
Technological developments can provide benefits if applied properly. Along with this, the need for technology is also very much needed in the medical world. With the condition of a large hospital, the large number of patients and the limited number of medical personnel and the demand for good patient care has always been a problem in every hospital. One of the problems is the provision of infusion fluids, in this research the aim is to make scientific work to realize designs, and programs, and determine the performance of Arduino Uno-based infusion fluid speed control devices, using the Weight Sensor (Load Cell) method as a detector for remaining infusion fluids, and using the NodeMCU8266 as a data transfer medium, as well as controlling the infusion flow rate using the Macro set and Micro set methods. After testing this device, it was found that this device worked well and was suitable for the research subject. This system is expected to make it easier for nurses in hospitals to monitor and replace infusion fluids